Multiple facets of rarity among rain forest trees in the Western Ghats of India. (December 2018) - Davidar, Priya; Munoz, François; Puyravaud, Jean-Philippe; Mohandass, D.; Ramachandran, V.S.
Abstract: We collated data on the latitudinal, elevation and seasonality ranges, local densities, stature and dispersal mode of 514 evergreen tree species (≥10 cm girth at breast height), including 317 endemics, from the rain forests of the Western Ghats (WG) of India using two complementary databases, (i) 68 tree inventory plots, and (ii) the Atlas of Endemics. We tested the hypotheses that (i) regional rarity would be associated with local rarity and narrower ecological amplitudes, (ii) shorter and mechanically dispersed trees would be rarer, (iii) higher proportion of endemic species would be rare (iv) regionally wide ranging species would be locally rare, and localised species would be denser, (v) families with single species would be relicts in this biome, (vi) larger families would have a higher proportion of rare and endemic species. We used Atlas records in a generalised least square model acknowledging phylogenetic relationships, to test hypotheses (i) to (ii), and non parametric tests for (iii) to (vi). We identified rare species using binary cut-offs and compared these with IUCN threat status. Rarity was associated with (i) narrower ecological amplitudes and shorter stature, independent of phylogeny, (ii) 18 wide ranging and locally sparse, 41 narrow ranging and locally dense species, (iii) relict species and families, (iv) larger families. Rare species were more likely to be threatened, but 39% were not evaluated. We identified zones of rare endemics to help with conservation planning. The WG rain forests have a unique evolutionary history and potential that require increased conservation measures. Highlights: We examined multiple facets of rarity among 514 species including 317 endemics from the Western Ghats of India. Rare species tend to have narrower ecological amplitudes, be short statured. Rare endemics, rare non-endemics and rarity among families is examined. The results highlight the importance of this limited biome for its unique biodiversity and evolutionary history.